2019
DOI: 10.1080/09613218.2019.1655630
|View full text |Cite
|
Sign up to set email alerts
|

Determining indoor environmental criteria weights through expert panels and surveys

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.-Users may download and print one copy of any publication from the public portal for the purpose of private study or research.-You may not further distribute the material or use it for any profit-making activity or commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Expert panels are widely used for weighing criteria and evaluating alternatives in MCDM techniques 28 . The expert panel in this study included 18 Ph.D. holders in Environmental Health Engineering with an experience in photocatalytic removal of persistent pollutants.…”
Section: Methodsmentioning
confidence: 99%
“…Expert panels are widely used for weighing criteria and evaluating alternatives in MCDM techniques 28 . The expert panel in this study included 18 Ph.D. holders in Environmental Health Engineering with an experience in photocatalytic removal of persistent pollutants.…”
Section: Methodsmentioning
confidence: 99%
“…Weights can be established in various ways, with different limitations depending on which data type is used to evaluate the potential consequences for occupants [12]. Some relative weight models prioritize health risks by using statistics associating exposure to a given condition; others prioritize perceived IE by relying on subjective occupant evaluations, while others still combine both approaches by asking topic experts for insight into both of the former [13]. Since there is no consensus in the literature and weights are very context-specific, we present the methodology without fixed weights but with the principle of relative weights integrated into the assessment architecture.…”
Section: Preliminary Methodology For Holistic Assessment Aggregationmentioning
confidence: 99%
“…However, other relevant research on different case studies concerning IEQ factors and/or their relationships were found for this review. For the sake of completeness, these pertinent studies are mentioned below: Chiang et al (2001) [74], Frontczak and Wargocki (2011) [75], Kim and de Dear (2012) [76], Catalina and Iordache [77], Sakhare and Ralegaonkar [78], Nimlyat and Kandar (2015) [79], Gadotti and Albatici (2016) [80], Ricciardi and Buratti (2018) [81], Nimlyat (2018) [82], Yang and Moon (2019) [83], Piasecki (2019) [84], Rohde et al (2020) [85], Piasecki et al (2020) [86], and Tang et al (2020) [87].…”
Section: Other Ieq Studiesmentioning
confidence: 99%